Visual and social differences in dyslexia: deep phenotyping of four cases with spared phonology. Issue 5 (3rd September 2022) - Palser, Eleanor R.; Miller, Zachary A.; Licata, Abigail E.; Yabut, Nicole A.; Sudarsan, Swati P.; Tee, Boon Lead; Deleon, Jessica A.; Mandelli, Maria Luisa; Caverzasi, Eduardo; Sturm, Virginia E.; Hendren, Robert; Possin, Katherine L.; et al.
ABSTRACT: Diagnostic criteria for dyslexia describe specific reading difficulties, and single-deficit models, including the phonological deficit theory, have prevailed. Children seeking diagnosis, however, do not always show phonological deficits, and may present with strengths and challenges beyond reading. Through extensive neurological, neuropsychological, and academic evaluation, we describe four children with visuospatial, socio-emotional, and attention impairments and spared phonology, alongside long-standing reading difficulties. Diffusion tensor imaging revealed white matter alterations in inferior longitudinal, uncinate, and superior longitudinal fasciculi versus neurotypical children. Findings emphasize that difficulties may extend beyond reading in dyslexia and underscore the value of deep phenotyping in learning disabilities.